(untitled) (Journal of Contemporary Philology, 2025)
The article examines two phonetic phenomena in the Balkan dialects of Macedonia: the restriction of accent placement to the last three syllables and double accentuation. These phenomena are characteristic of the Macedonian-Albanian-Greek area at the center of the Balkan Sprachbund. The author disagrees with the widely accepted thesis in Balkan literature that the western and central Macedonian dialects share a common accentual system with the Greek, Aromanian, and Albanian dialects in this region. The article presents arguments that challenge previous views on the central Balkan nature of the restriction of accent placement to the last three syllables. The author argues that this phenomenon does not merit special attention, as it represents a universal tendency driven by natural linguistic preferences. Regarding double accentuation, the author identifies a specific type of this phenomenon that may be considered a distinct Balkan trait. This type of accentuation is characteristic of a Balkan micro-region where Slavic and Greek dialects are in contact.